Body mass index and lipid levels in children from Ankara, Turkey versus Bogalusa, Louisiana - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2005)
Background. Turkish Heart Study demonstrated that low high density lipoprotein cholesterol levels are prevalent among Turkish adults. Methods. We compared body mass index and lipid levels of Turkish children (n = 1525, ages 10-17) with the bi-racial community of Bogalusa Heart Study. Results. Turkish children have lower body mass index than American children (19.0 +/- 3 kg/m(2) for Turkish girls, 20.2 +/- 4 for White American girls, 20.9 +/- 5 for African American girls; and 18.9 +/- 3 kg/m(2) for Turkish boys, 20.2 +/- 4 for White American boys, 20.0 +/- 4 for African American boys, P < 0.01). Turkish children have higher triglyceride and lower high density lipoprotein cholesterol levels despite their lower body mass index. High density lipoprotein cholesterol levels (mmol/L) are 1.3 +/- 0.3 for Turkish girls and boys versus 1.4 +/- 0.5 for White American girls and boys, versus 1.6 +/- 0.5 and 1.7 +/- 0.5 for African American girls and boys, respectively (P < 0.01). Triglyceride levels (mmol/L) are 1.0 +/- 0.6 and 1.0 +/- 0.5 for Turkish girls and boys versus 0.9 +/- 0.5 and 0.8 +/- 0.5 for White American; and 0.7 +/- 0.3 for African American girls and boys, respectively (P < 0.01). Conclusions. Our observation of a lower HDL-C and a higher TG level in Turkish children (despite their lower BMI) is of interest and may indicate that unique characteristics in lipoprotein levels of Turkish adults start early in life. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: body mass index; lipid levels; children; HIGH-DENSITY-LIPOPROTEINS; ELEVATED HEPATIC LIPASE; CHOLESTEROL; TURKISH; HDL; POPULATION; OBESITY; PLASMA; SERUM